Ataxia and Weakness after Sleeve Gastrectomy: A Case Report - Shil, Rajish Sanjit Kumar; Alomar, Ammar Fadhil; Farooqui, Mohammad Rashid (Highlights on Medicine and Medical Science Vol. 3, 2021)
Every year, the number of patients undergoing bariatric surgery grows, as obesity has become a leading cause of a variety of comorbidities. The frequency of complications associated with this procedure has been increasing. We present the case of a 32-year-old man who suffered ataxia and peripheral polyneuropathy after a sleeve gastrectomy operation, then developed progressive weakness in his extremities within 8 months of surgery and was admitted to the hospital for neurological consultation and care. This uncommon neurological complication might have been due to rapid weight loss and vitamin deficiency. The case report focuses on the signs that bariatric surgeons should look for and how they should treat them.